THE IDENTIFICATION OF MONEY LAUNDERING ON DRUG TRAFFICKING - Lucky Nurhadiyanto (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
Drug trafficking is a holistic process. The involvement of various parties linked with law enforcement efforts. The number of drug trade reaches millilons of tons. This number equivalent to billions of fund that circulating in trading transactions. The one alternative ways to eradicate drug trafficking is to track the cash flow. Because of the financial transactions as the main chain to running this business. Tracking the flow of drug trafficking funds through money laundering approach can be done by indetifying various placement, layering, and integration activities of suspicious financial transactions. The placement pattern becomes the entrance of financial transactions through the participation of the providers of financial services. The layering pattern can consist od smurfing, money changer, and buying a stock portofolio. Meanwhile, the integration pattern enters various business activities with minimal risk. The prediction of money laundering tren based on drug trafficking leads three aspects, that is utilization of technologies, the role of third parties, and the involvement of unscrupulous government and law enforcement.